Human Resource Development and Employee Engagement in Nepalese Development Banks - Niraula, Ganesh Pd.; Kharel, Shreekrishna (Tribhuvan University Journal, 2023)
The purpose of this study is to determine how employee engagement in Nepalese development banks is affected by human resource development. The study’s independent variables include employee training, personal development, career development, and professional development. The dependent variable in the study is employee engagement. The research design is descriptive research design. The population of the study consisted of 18 development banks, and a simple random sample technique was used to select the employees of 7 development banks at random basis. Data collected using a standardized questionnaire on Likert Scale with1 signifying a strong agreement and 5 a strong disagreement. Descriptive statistics, correlation, and regression analysis are used to analyze the data. Cronbach’s Alpha has been used to test for reliability. Reliability is acceptable with a Chronbach’s Alpha rating of 0.71 on an average. The study concludes that employee training facilities and personal development have a favorable and significant relationship with employee engagement; career development has a negligible and insignificant impact on employee engagement. Professional development has a negligible yet significant impact on employee engagement.